Multiple aspects of word knowledge in Thai EFL students : the hierarchical acquisition and relationships - Worakrit Nontasee,; Apisak Sukying, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research explored the nature of the word knowledge construct by analyzing the hierarchical difficulty in acquiring different word knowledge aspects and their relationships. The research examined Nation’s (2013) framework, which is the most widely accepted conceptualization of what is involved in knowing a word. Therefore, this article presents the hypothesized concept of knowing a word as a multi-aspect construct. A battery test of word knowledge aspects was administered to 500 senior high school participants who were English as a Foreign Language (EFL) students in Thailand. The results showed that the receptive knowledge test of an aspect showed higher scores than its productive knowledge test. There was also a positive correlation between knowledge of the different aspects. Besides, an analysis of Implicational Scaling (IS) illustrated a valid implicational pattern of word knowledge aspects and found that productive knowledge could be known without complete mastery of all aspects of receptive knowledge. Finally, a Structural Equation Modeling (SEM) analysis demonstrated the benefit of the various word knowledge aspects to acquiring word knowledge. Overall, the current research corroborates previous evidence for the vocabulary acquisition pattern and the conceptualization of word knowledge and provides empirical evidence in a Thai EFL context. It also implies that word knowledge is acquired along a developmental learning continuum.